BUILDING EFFECTIVE ORGANIZATIONAL COMMUNICATION - Agung Anggara; Vira Septria; Salsalliah Albant Triswandi; Meri Merisa; Muhammad Farhan Fadilla (Universitas Efarina, 2024)
Effective organizational communication is a key element in achieving a company's long-term goals. This research examines the importance of communication in organizations and its impact on company performance. The research method used is descriptive analysis to describe existing communication phenomena. Results show that good communication increases collaboration, reduces misunderstandings, and creates a positive work culture. With the right communication strategy, organizations can ensure every individual understands the company's vision and mission, as well as their role in achieving it. Communication training and a positive feedback culture are essential to improving communication skills in the modern work environment. This research concludes that investment in effective communication has a positive effect on productivity, employee morale, and overall organizational success